Biological activities of Cremaspora triflora (Thonn.) K. Schum (Rubiaceae) extract, fractions and an isolated compound on selected fungi and bacteria and the determination of the mode of action using Electron Microscopy - Botha, Francien Susanna S. (2026)
Thesis (PhD (Paraclinical Sciences))--University of Pretoria, 2016.